THE EFFECT OF VARIATION OF MIXTURE OF IJUK FIBER AND COCONUT FIBER WITH EPOXY MATRIX ON THE MECHANICAL STRENGTH OF COMPOSITE (Journal of Renewable Energy and Mechanics, 2025)
Fibre-based composites continue to be investigated and developed as alternative materials to replace metals, primarily due to their advantageous properties of high strength and lower weight compared to metals. This study aims to fabricate fibre composites using ijuk fibres and coconut coir fibres as a matrix with epoxy resin. In this research, mixtures of ijuk fibres, coconut coir fibres, and epoxy resin were prepared in proportions of 20%:30%:50%, 25%:25%:50%, and 30%:20%:50%. The highest bending strength test results were obtained in specimen 3, which consisted of a mixture of 30% palm fibre, 20% coconut fibre, and 50% epoxy resin.  This specimen had a tensile strength value of 18.93 MPa and an impact value of 0.387 Joules/mm². This result can be attributed to the increasing proportion of ijuk fibres and the decreasing proportion of coconut coir fibres within the epoxy resin matrix, which influences the elastic strain of the fibre core (cellulose). The higher cellulose content of ijuk fibres enhances bending strength and impact resistance. This is supported by the impact (Charpy) test results, where specimen 3 (30%: 20%:50%) exhibited the highest bending and impact strength. Conversely, increasing the proportion of coconut coir fibres reduced the impact strength. The fracture morphology revealed that specimen 1 exhibited a brittle fracture, whereas specimens 2 and 3 exhibited a fibrous brittle fracture.